Case Report: Hemoptysis Caused by Pulmonary Tuberculosis Complicated With Bronchial Artery-Pulmonary Artery Fistula in Children - Huihui Zhu; Fangfang Lv; Ming Xu; Shunhang Wen; Yangming Zheng; Hailin Zhang (Frontiers Media S.A., 2021)
Bronchial artery-pulmonary artery fistula secondary to pulmonary tuberculosis is an important cause of hemoptysis in adults, but it's relatively rare in children. Bronchial artery-pulmonary artery fistulas are mostly congenital in children and may have no clinical manifestations in the early stage. Congenital bronchial artery-pulmonary fistula with pulmonary tuberculosis can lead to hemoptysis. From 2016 to 2020, two children with pulmonary tuberculosis complicated with bronchial artery and pulmonary artery fistula were admitted and treated in our hospital. We reminded pediatricians to pay attention to a variety of etiology combined with the possibility of children's hemoptysis.